Odpowiedzi

Najlepsza Odpowiedź!
2010-03-23T20:44:06+01:00
1/6x + 1/3x + x - 3/5x + 1 = x |*30
5x+10x+30x-18x+30=30x
27x+30=30x
27x-30x=-30
-3x=-30|:(-3)
x=10
1 5 1
2010-03-23T20:45:31+01:00
1/6x + 1/3x + x - 3/5x + 1 = x wspólny mianownik = 30x
5 + 10 + 30x² - 18 + 30x = 30x²
30x² - 30x² + 30x = 18 - 5 - 10
30x = 3
x = 3/30 = 1/10 = 0,1
2010-03-23T20:47:30+01:00
1/6x + 1/3x + x - 3/5x + 1 = x
5/30x + 10/30x + x - 18/30x + 1 = x
-3/30x + x + 1 = x
9/10x + 1 = x / -9/10x
1 = 1/10x / razy10 (nie oznaczam razy 'x' po sobie można pomylić)
x = 10